Description of a new species of Anisitsiellidae Koenike, 1910 (Acari, Hydrachnidia), the first record of the family from China - Yi, Tianci; Jin, Daochao; Guo, Jianjun (Zootaxa, 2009)
Considering the geographical location of China, a very rich fauna of water mites should be expected. Previously, seventeen families have been reported from China (Jin, 1997; Smit, 2002; Guo & Jin, 2005): Eylaidae Leach, 1815, Limnocharidae Grube, 1859, Hydryphantidae Piersig, 1896, Hydrodromidae Viets, 1936, Hydrachnidae Leach, 1815, Sperchontidae Thor, 1900, Lebertiidae Thor, 1900, Oxidae Viets, 1926, Teutoniidae Koenike, 1910, Limnesiidae Thor, 1900, Hygrobatidae Koch, 1842, Unionicolidae Oudemans, 1909, Pionidae Thor, 1900, Mideopsidae Koenike, 1910, Arrenuridae Thor, 1900 and Pontarachnidae Koenike, 1910. The species described in this paper belongs to the subgenus Dartia Soar, 1917 in the genus Nilotonia Thor, 1905 of the family Anisitsiellidae Koenike, 1910, which increases the number of known water mite families in the Chinese fauna to eighteen.